2019
DOI: 10.15314/tsed.547406
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of different stretching protocols on flexibility, yoyo IR-1 and repeated sprint ability performance

Abstract: The purpose of this study was to examine the acute effect of different stretching protocols on flexibility, Yo-Yo IR-1 and repeated sprint performance. The sample group of this study consists of 15 male who were doing regular exercise at least 3 years. This group performed 5 different stretching protocols on non-consecutive days. Stretching protocols were determined as follows: light jogging for only 5 minutes (NS), light jogging and static strectching (SS), light jogging and dynamic stretching (DS), light jog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The stretching types and their combinations used during warm-up were verified by Kafkas et al (2019). They tested a group of 15 men that were regularly involved in physical activities: jogging + NS, jogging + SS, jogging + DS, jogging + SS+DS, jogging + DS + SS, with a duration of 5 minutes.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…The stretching types and their combinations used during warm-up were verified by Kafkas et al (2019). They tested a group of 15 men that were regularly involved in physical activities: jogging + NS, jogging + SS, jogging + DS, jogging + SS+DS, jogging + DS + SS, with a duration of 5 minutes.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…The results of the anthropometric measurements for the participants are presented in Table 1, which displays the mean and standard deviation for each group. Participants were given instructions to refrain from engaging in different types of exercises on the day preceding the measurements, to avoid consuming stimulating beverages such as tea, coffee, alcohol, and carbonated drinks, and to have their last meal at least 2 hours before the measurements were conducted, following the guidelines outlined by Kafkas et al [23].…”
Section: Methodsmentioning
confidence: 99%
“…Prior to the 1-RM test, all participants engaged [23]. Participants were given the autonomy to select their initial weights for the 1-RM test according to their personal preference.…”
Section: Maximal Repetition Squat Test (1-rm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Matthys et al (2013) found that top young handball players outperformed non-elite players on speed tests. Kafkas et al (2019) reported considerable progress in the 30 m sprint with additional days of training. As he assessed the yearly growth of biomotor features in collegiate volleyball players during a two-year training and competition cycle.…”
Section: Speedmentioning
confidence: 96%